TEACHERS’ PERSPECTIVE TOWARDS THE USE OF INTERNET FOR FINDING THE MATERIAL IN ENGLISH LANGUAGE TEACHNG AND LEARNING - Wirdayani, Tia; Salam, Urai; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This study aims to describe the teachers’ perspective towards the use of Internet in English language teaching and learning. The subjects of this study were eight English teachers from three junior high schools in different locations. This research used case study, involves three instruments such as, demographic question, questionnaire and interview, and described triangulation data to the findings. Based on the findings, the teachers had positive perspectives in using Internet as the appropriate tool for finding the material although some of them did not use Internet. The teachers who did not use Internet stated that they did not have Internet ability because they did not well-trained in using it. Particularly, the case was caused by the teachers’ age and teaching period. Even though, they were old generations, they were interested in using Internet. In order to improve their Internet skills, they needed training. Key words: Teachers’ Perspective, English Language Teaching, Internet Abstrak: Penelitian ini bertujuan untuk menggambarkan pengalaman guru dan kepercayaan guru terhadap penggunaan media Internet dalam pembelajaran bahasa Inggris. Partisipan dalam penelitian ini adalah delapan orang guru SMP dari tiga sekolah yang berbeda. Penelitian ini menggunakan metode studi kasus dengan menggunakan instrumen pertanyaan demograpik, kuisioner dan wawancara dan menjabarkan semua instrument tersebut di bagian temuan penelitian. Berdasarakan hasil penelitian, guru tersebut mempunyai pandangan yang positif terhadap penggunaan Internet sebagai media yang tepat dalam mencari materi meskipun beberapa dari guru tersebut tidak menggunakan Internet. Guru yang tidak menggunakan Internet menyatakan bahwa mereka tidak mempunyai kemampuan berinternet karena mereka tidak terlatih dengan baik dalam menggunakan Internet.hal ini disebabkan oleh faktor usia dan pengalaman mengajar. Meskipun mereka termasuk generasi tua, mereka tetap tertarik dengan penggunaan Internet. Untuk meningkatkan kemampuan Internetnya, guru tersebut membutuhkan pelatihan. Kata kunci: Pandangan guru, pembelajaran bahasa Inggris, Internet